Compounds producing an effective combinatorial regimen for disruption of HIV‐1 latency. Issue 2 (15th December 2017) - Hashemi, Pargol; Barreto, Kris; Bernhard, Wendy; Lomness, Adam; Honson, Nicolette; Pfeifer, Tom A; Harrigan, P Richard; Sadowski, Ivan
Abstract: Highly active antiretroviral therapy (HAART) has improved the outlook for the HIV epidemic, but does not provide a cure. The proposed "shock‐and‐kill" strategy is directed at inducing latent HIV reservoirs, which may then be purged via boosted immune response or targeting infected cells. We describe five novel compounds that are capable of reversing HIV latency without affecting the general T‐cell activation state. The new compounds exhibit synergy for reactivation of latent provirus with other latency‐reversing agents (LRAs), in particular ingenol‐3‐angelate/PEP005. One compound, designated PH02, was efficient at reactivating viral transcription in several cell lines bearing reporter HIV‐1 at different integration sites. Furthermore, it was capable of reversing latency in resting CD4 + T lymphocytes from latently infected aviremic patient cells on HAART, while producing minimal cellular toxicity. The combination of PH02 and PEP005 produces a strong synergistic effect for reactivation, as demonstrated through a quantitative viral outgrowth assay (qVOA), on CD4 + T lymphocytes from HIV‐1‐infected individuals. We propose that the PH02/PEP005 combination may represent an effective novel treatment for abrogating persistent HIV‐1 infection. Synopsis: HIV‐1 latency is the major obstacle to developing a permanent cure. The shock and kill strategy aims to eliminate latent HIV reservoirs by exposing infected cells. This study reveals new compounds that reverse HIV‐1 latency, demonstrated through in vitro and ex vivo investigation. High‐throughput screening identified PH compounds that exhibit HIV latency reversing activity when examined on latently infected reporter cell lines and on resting CD4 + T cells purified from aviremic HIV‐1 infected patients on antiretroviral therapy. PH compounds are capable of reversing latency without affecting global T‐cell activation states. PH compounds exhibit a significant synergistic effect when combined with other known latency reversing agents. In particular, PH02 combined with PEP005/ingenol‐3‐angelate show promising latency reversing activity at clinically relevant concentrations, which is demonstrated through quantitative viral outgrowth assays on CD4 + T lymphocytes purified from HIV‐infected individuals on therapy. Abstract : HIV‐1 latency is the major obstacle to developing a permanent cure. The shock and kill strategy aims to eliminate latent HIV reservoirs by exposing infected cells. This study reveals new compounds that reverse HIV‐1 latency, demonstrated through in vitro and ex vivo investigation.